Auroras during extreme geomagnetic storms: Visual observations of the SAR arc in Irkutsk during the 1859 Carrington event - Mikhalev Aleksandr; Beletsky Aleksandr (Solar-Terrestrial Physics)
The paper analyzes the description in chronicles of the September 2, 1859 auroras observed in Irkutsk during the Carrington event. The description of the red arc by an eyewitness, the analysis of geomagnetic conditions, publications on visual observations of auroras of various forms at middle and low latitudes during this period, modern instrumental observations of SAR arcs at the latitude of Irkutsk have allowed us to assume that the red arc described in the chronicles is a SAR arc — one of the auroral types at subauroral and middle latitudes observed during geomagnetic storms. We have established that in Irkutsk the SAR arc was observed during the recovery phase of the magnetic superstorm. The intensity of the SAR arc was estimated at ~10–20 kR. The projection of the plasmapause onto the ionosphere on September 2, 1859 at ~12 UT was at the latitude of Irkutsk. We can assume that the description of the aurora borealis on September 2, 1859 in Irkutsk is the first objective description of the SAR arc, a century before its discovery as a phenomenon in 1958.